Labour rights in Peru and the EU trade agreement: Compliance with the commitments under the sustainable development chapter - Jan Orbie; Lore Van den Putte (Austrian Foundation for Development Research (ÖFSE), 2016)
European Union (EU) trade policy has become increasingly contested and politicised. Citizens and politicians have become more and more concerned about the human rights and sustainable development implications of free trade. The European Commission in its 'Trade for All' Strategy has recognized the need for a more value-based trade policy. In the same vein, the EU has included a chapter on Trade and Sustainable Development in recent free trade agreements. However, there is still much uncertainty about the specifics of these legal commitments and about their implementation in practice. In this study, we aim to assess the labour rights commitments in the EU-Peru-Colombia agreement, with a specific focus on Peru and the agricultural sector. Based on an analytical framework that summarises the labour-related commitments of the sustainable development Title into three categories - upholding ILO Core Labour Standards, non-lowering domestic labour law, and promoting civil society dialogue - we conclude that Peru has failed to comply in a number of areas. We also make recommendations for the EU and civil society and suggestions for more profound and systematic research. – – Diese Studie zeigt, dass sowohl die Peruanische Regierung als auch die EU ihre Bemühungen verstärken könnten, die in ihren Handelsabkommen enthaltenen Verpflichtungen zum Thema Arbeitsnormen einzuhalten, und die Zivilgesellschaft in dieser Hinsicht eine wichtige Rolle spielen könnte. Die Europäische Handelspolitik ist zunehmend umstritten geworden. In Reaktion darauf hat die Europäische Union (EU) in ihren jüngsten Handelsabkommen ein Kapitel zur nachhaltigen Entwicklung aufgenommen, welches Bestimmungen zu den Themen Arbeitsund Umweltschutz enthält. Dies ist unter anderem der Fall für das EU-Peru-Kolumbien Handelsabkommen, das im Jahr 2013 in Kraft getreten ist. Während das Abkommen ein Kapitel zur nachhaltigen Entwicklung enthält und obwohl die Achtung von Arbeitsnormen in Peru allgemein recht gering ist, ist die Einhaltung der Verpflichtungen zu Arbeitsnormen durch Peru im Rahmen des Abkommens bislang nicht untersucht worden. Wir konzentrieren uns in unserer Untersuchung auf den landwirtschaftlichen Exportsektor im breiteren Kontext von Arbeitsnormen. [...]
Keywords: 330; Peru; labour; European Union; trade